Geographical Information Systems for managing the customer value / Abdul Manaf Bohari, Ruslan Rainis and Malliga Marimuthu - Bohari, Abdul Manaf; Rainis, Ruslan; Marimuthu, Malliga (2010)
Geographical Information Systems is widely used and applied in the real world business operation because of it capabilities to manage customer, by visualizing customers value in the geographical platform. The increase of GIS usage for managing customers are become new approaches to business because this technology can cope with the real environment of marketplace. Because of managing the customer in the marketplace are become more challenge, especially in the economic meltdown situation, Geographical Information Systems are identified as a new resources for helps business to deal with customers challenges. This paper discussed the usage of Geographical Information Systems with specific concentrate on application, tools and benefits. Finally, future prospect of Geographical Information Systems will discussed with priority on the latest application and tools for managing customer in the real marketplace.